Screening for Hepatitis B and Sphylis in the Working Area of the Waena Health Center - Hasmi, Hasmi; Makaba, Sarce; Lazarus Rumboirusi, Ricky (Jurnal Pengabdian Masyarakat Bestari, 2024)
This service aims to detect Hepatitis B and Syphilis in pregnant women. The form of activity is to screen pregnant women using the Hepatitis B and Syphilis Rapid Diagnosis test kit, then pre and post screening counseling is provided. screening activity  from May 16 to June 16, 2024.. The results of the service were obtained from 87 pregnant women who were screened, 4 people tested positive for Hepatitis B (4.6%) and 5 people tested positive for Syphilis (5.7%), this result is considered high. Pregnant women with the highest positive hepatitis B are <25 years old, Papuan ethnicity, high school education, highest pregnant women's occupation Housewives (IRT) and unmarried status. Pregnant women with the highest positive Sphylis are <25 years old, Papuan tribe, junior high school graduation education, the highest private pregnant women's occupation and unmarried status.